Differences in career longevity before and after implementation of the Women`s Tennis Association Tour Age Eligibility Rule and Player Development Programmes: a 25-year study - Otis, C. L.; Hainline, B.; Harwood, C.; Jayanthi, N. A.; Jensen, R.; Keber, A.; Kroshus, E.; Livengood, T.; Stroia, K.; Quinn, A.; Vitkova, S.; Kliethermes, S. A. (British Journal of Sports Medicine, 2022)
Objectives: To assess differences in career longevity, as a potential marker of athlete well-being, before and after the 1995 implementation of the Women`s Tennis Association (WTA) Age Eligibility Rule (AER) and Player Development Programmes (PDP), which focused on organisational, physical and psychosocial education, skill building and support for adolescent athletes (=17 years).Methods: Career longevity data were collected through 2019 on adolescent players who began professional tournament play between 1970 and 2014 and reached a WTA singles ranking of 1-150 for a minimum of 1 week during their careers. Players were separated into pre-AER/PDP and post-AER/PDP groups, consisting of those who played their first professional events (FPE) before or after 1 January 1995. Measures of career longevity included career duration and premature retirement.Results Eight-hundred and eleven players were included in this study (51% pre-AER/PDP). The median career duration was 14.2 years for the post-AER/PDP group compared with 12.1 years for the pre-AER/PDP group (p<0.001). Moreover, post-AER/PDP players had higher probabilities of 10-year and 15-year careers compared with pre-AER/PDP players. After adjusting for age at FPE, athletes in the pre-AER/PDP group had an increased risk of shorter career duration (HR 1.55; 95% CI 1.31 to 1.83) and increased odds of premature retirement (OR 5.39; 95% CI 2.28 to 12.75) than athletes in the post-AER/PDP group. Conclusions: Adolescent athletes participating on the WTA after the combined AER/PDP initiative had longer career durations, higher probabilities of 10-year and 15-year careers, and decreased risk of premature retirement compared with those participating prior to AER/PDP. Organisational practices that encompass both education and competition regulation can positively affect career longevity related to improving athlete well-being.